If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 7(-4x + 11) = -109 Reorder the terms: -3x + 7(11 + -4x) = -109 -3x + (11 * 7 + -4x * 7) = -109 -3x + (77 + -28x) = -109 Reorder the terms: 77 + -3x + -28x = -109 Combine like terms: -3x + -28x = -31x 77 + -31x = -109 Solving 77 + -31x = -109 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-77' to each side of the equation. 77 + -77 + -31x = -109 + -77 Combine like terms: 77 + -77 = 0 0 + -31x = -109 + -77 -31x = -109 + -77 Combine like terms: -109 + -77 = -186 -31x = -186 Divide each side by '-31'. x = 6 Simplifying x = 6
| 8(5f+4)= | | -x+15=14x-20 | | 9(p-1)= | | 133=3x+5(3x-13) | | 4x-8=-2x-8 | | 5(3(x+2)+4)+2x=67 | | y=4.8+1.2 | | X=y+1.10 | | -75=-2x-3(-3x+11) | | (1.6+x)=X+8.7 | | h=-16t^2+14t+10 | | 2x+4(4x-11)=64 | | (113-x)/2=30 | | A=28x-x^2 | | 7x+5(3x-17)=113 | | 8-6x=34 | | 6x+3=5x-16 | | 5x+2(4x-17)=83 | | 4x-16=28+36 | | x+x-5.3=718.7 | | 3y+30y=3 | | 9x^2-2y^2+18=0 | | -50=4m-2 | | 3x+3(3x-5)=45 | | -20+14=m-4 | | 3x+12=2x+15 | | 38x-4=5 | | 8-6x=37 | | -3y+5=-25 | | 25+0.25(65)= | | 100=x-0.15x | | x^2+x/6-2.5+0 |